KESANTUNAN BERBAHASA PADA NOVEL BULAN KARYA TERE LIYE (KAJIAN PRAGMATIK): KESANTUNAN BERBAHASA PADA NOVEL BULAN KARYA TERE LIYE (KAJIAN PRAGMATIK) - Jodi Pranata (Anafora: Jurnal Penelitian Mahasiswa Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to identify language politeness in the novel "Bulan" by Tere Liye. The method used in this research uses descriptive qualitative. The data source in this research is the novel "Bulan" by Tere Liye. The theory used in this research uses the pragmatic theory of language politeness. The research data collection technique was carried out by reading the entire contents of the novel, carefully recording the data obtained from the novel, grouping the data based on language politeness maxims and analyzing the data obtained systematically. The results of the discussion in this research found various kinds of politeness maxims in language including (a) Maxims of Wisdom, totaling 20 (b) Maxims of Generosity totaling 8 (c) Maxims of Appreciation totaling 12 (d) Maxims of Simplicity totaling 8 (e) Maxims of Consensus totaling 5 (f ) The Maxim of Sympathy is 6.